Persistence with dual antiplatelet therapy after percutaneous coronary intervention for ST-segment elevation acute coronary syndrome: a population-based cohort study in Catalonia (Spain) - Helena Tizón-Marcos; Josepa Mauri; Alba Rosas; M Hernandez; L Recasens; Aida Ribera; Ignacio Ferreira-Gonzalez; Josep Ramon Marsal; Gerard Oristrell; Maria Teresa Faixedas; Sergio Rojas; Carlos Labata; et al. (BMJ Open)
Objectives Guidelines recommending 12-month dual antiplatelet therapy (DAPT) in patients with ST-elevation acute coronary syndrome (STEACS) undergoing percutaneous coronary intervention (PCI) were published in year 2012. We aimed to describe the influence of guideline implementation on the trend in 12-month persistence with DAPT between 2010 and 2015 and to evaluate its relationship with DAPT duration regimens recommended at discharge from PCI hospitals.Design Observational study based on region-wide registry data linked to pharmacy billing data for DAPT follow-up.Setting All PCI hospitals (10) belonging to the acute myocardial infarction (AMI) code network in Catalonia (Spain).Participants 10 711 STEACS patients undergoing PCI between 2010 and 2015 were followed up.Primary and secondary outcome measures Primary outcome was 12-month persistence with DAPT. Calendar year quarter, publication of guidelines, DAPT duration regimen recommended in the hospital discharge report, baseline patient characteristics and significant interactions were included in mixed-effects logistic regression based interrupted time-series models.Results The proportion of patients on-DAPT at 12 months increased from 58% (56–60) in 2010 to 73% (71–75) in 2015. The rate of 12-month persistence with DAPT significantly increased after the publication of clinical guidelines with a time lag of 1 year (OR=1.20; 95% CI 1.11 to 1.30). A higher risk profile, more extensive and complex coronary disease, use of drug-eluting stents (OR=1.90; 95% CI 1.50 to 2.40) and a 12-month DAPT regimen recommendation at discharge from the PCI hospital (OR=5.76; 95% CI 3.26 to 10.2) were associated with 12-month persistence.Conclusion Persistence with 12-month DAPT has increased since publication of clinical guidelines. Even though most patients were discharged on DAPT, only 73% with potential indication were on-DAPT 12 months after PCI. A guideline-based recommendation at PCI hospital discharge was highly associated with full persistence with DAPT. Establishing evidence-based, common prescribing criteria across hospitals in the AMI-network would favour adherence and reduce variability.